A Systematic Review of Efficacy and Safety of Plasma-Derived von Willebrand Factor/Factor VIII Concentrate (Voncento) in von Willebrand Disease - Rugeri, Lucia; Thomas, Will; Schirner, Kathrin; Heyder, Lisa; Auerswald, Günter (Thrombosis and Haemostasis, 2024)
Background For the treatment of von Willebrand disease (VWD), von Willebrand factor (VWF) concentrates can be used in on-demand, long-term prophylaxis, and surgical prophylaxis regimens.Methods This systematic literature review was conducted to evaluate the efficacy, consumption, and safety of plasma-derived human coagulation FVIII/human VWF (pdVWF/FVIII; Voncento/Biostate) for the treatment of patients with any inherited VWD type. An electronic search was conducted in MEDLINE and Cochrane Library databases on VWD therapies. All retrieved publications were assessed against predefined inclusion/exclusion criteria following the Cochrane group recommendations. Associated pharmacovigilance data were collected across the same time period.Results Eleven publications from eight study cohorts were identified for data retrieval. All were from multicenter studies and included both pediatric and adult patients. Eight publications included evaluations of the efficacy of pdVWF/FVIII for on-demand treatment, eight included long-term prophylactic treatment, and eight included surgical prophylaxis. Treatment protocols and VWF administration methods differed between studies, as did safety evaluations. The clinical response was rated as excellent/good for on-demand treatment in 66 to 100% of nonsurgical bleeds, 89 to 100% in the treatment of breakthrough bleeds during long-term prophylaxis treatment, and hemostatic efficacy in surgical procedures was 75 to 100%. Pharmacovigilance data confirmed a low incidence of adverse events in treated patients.Conclusion This review provides a comprehensive summary of studies that evaluated the use of pdVWF/FVIII in VWD demonstrating the long-term effectiveness and safety of this pdVWF/FVIII across all ages, types of VWD, and treatment settings.
Keywords: blood products; factor VIII; systematic review; von Willebrand disease; von Willebrand factor